Analisis Kinerja Redaman Gelombang pada Breakwater Tenggelam Tipe Berlubang Dengan Pemodelan Fisik 2D - Andika, Ivana Aprili; Tugiono, Subuh; Zakaria, Ahmad; Wahono, Endro P. (Jurnal Rekayasa Sipil dan Desain (JRSDD), 2021)
Loss of land due to coastal erosion that occurs naturally by wave abrasion. Therefore, to protect the coast from erosion or other matters, a breakwater is needed which destroys the energy of the waves before reaching the shore. This is the background of the author in taking the title of the thesis about the Performance Analysis of Wave Attenuation in the Hollow Type Breakwater Submerged Type 2-D Physical Modeling. The variables used in this study were incident wave height (Ho), calm water level (ds), and breakwater type. The results of this study indicate that the damping coefficient (Cr) was obtained using a sinking breakwater without a hole with a calm water level (ds) of 2 cm of 0.479 which is the most effective damping produced in an experiment using a breakwater that is free from calm water surface (ds). 2 cm. The wave attenuation obtained from the wave defraction test using 2 types of breakwaters resulted that the breakwater without the damping hole was greater than using a perforated breakwater.